(untitled) (Czech Journal of International Relations, 1967)
Behind the various, more extreme evaluations and sometimes information taken out of context, the need to investigate and evaluate the basic tendencies that are realized in the dramatic and contradictory development of the situation in CER is beginning to emerge. It can be objected that our news coverage, and even journalism for the most part, provides little evidence of such an approach, stimulating not only for research, but also for practice and propaganda. In the following lines, however, they can inform you about the content of the event, which until recently was not customary to organize in this region. The wider context of the current Chinese development was therefore dealt with by the national seminar of the Central Scientific and Methodical Council for International Relations issues at the Socialist Academy on March 16 and 17, 1967 in Zivohost.